The Novel Angiotensin-(1–7) Analog, A-1317, Improves Insulin Resistance by Restoring Pancreatic β-Cell Functionality in Rats With Metabolic Syndrome - Barbosa, Maria Andréa; Barbosa, Claudiane Maria; Lima, Taynara Carolina; Santos, Robson Augusto Souza dos; Alzamora, Andréia Carvalho (Frontiers in Pharmacology, 2020)
In previous studies we have shown that oral Ang-(1-7) has a beneficial therapeutic effect on cardiometabolic disturbances present in metabolic syndrome (MetS). Based on the fact that Ang-(1-7) acts through release of nitric oxide (NO), a new peptide, A-1317 was engineered adding the amino acid L-Arginine, the NO precursor, to the N-terminal portion of the Ang-(1-7). Therefore, in a single molecule the substrate and the activator of NO are combined. In the present study, we evaluated the effect of A-1317 oral treatment on the liver-glucose metabolism in MetS induced by high fat (HF) diet in rats. Rats were subjected to control (AIN-93M, CT) or HF diets for 15 weeks to induce MetS and treated with A-1317, Ang-(1-7) included into hydroxypropyl-β-cyclodextrin (HPβCD) or empty HPβCD (E), in the last 7 weeks. At the end of 15 weeks, hemodynamic, biometric and biochemical parameters, redox process and qRT-PCR gene expression of NO synthase and RAS components were evaluated in the liver. HF/E rats increased gain body mass, adiposity index, despite the reduction in food intake, increased plasma leptin, total cholesterol, triglycerides, ALT, fasting blood glucose, OGTT and insulin, HOMA-IR and MAP and HR Furthermore, the MetS rats presented increased in liver angiotensinogen, AT1R, ACE mRNA gene expression and concentration of MDA and carbonylated protein. Both, Ang-(1-7) and A-1317, oral treatment in MetS rats reverted most of these alterations. However, A-1317 was more efficient in reducing body mass gain, ALT, AST, total cholesterol, insulin, fasting blood glucose, ameliorating β cell capacity by increasing HOMA-β and QUICKI whereas Ang-(1-7) reduced HOMA-β and QUICKI. In addition, Ang-(1-7) increased Mas and AKT liver mRNA gene expression, while A-1317 increased both Mas and MRGD and AMPK liver mRNA gene expression, suggesting a distinct pathway of action of Ang-(1-7) and A-1317 in MetS rats. Taken together, our data showed that treatment with A-1317 was able to ameliorate MetS disorders and suggest that this effect was mainly via MRGD via activation of AMPK and increasing β cell function.